2007
DOI: 10.1021/es0709831
|View full text |Cite
|
Sign up to set email alerts
|

Open Air Biocathode Enables Effective Electricity Generation with Microbial Fuel Cells

Abstract: The reduction of oxygen at the cathode is one of the major bottlenecks of microbial fuel cells (MFCs). While research so far has mainly focused on chemical catalysis of this oxygen reduction, here we present a continuously wetted cathode with microorganisms that act as biocatalysts for oxygen reduction. We combined the anode of an acetate oxidizing tubular microbial fuel cell with an open air biocathode for electricity production. The maximum power production was 83 +/- 11 W m(-3) MFC (0.183 L MFC) for batch-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
208
8
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(231 citation statements)
references
References 30 publications
14
208
8
1
Order By: Relevance
“…The reduction of oxygen at the cathode of MFCs is recognized as one of the current bottlenecks in power production [19,[130][131][132]. Oxygen is an ideal acceptor for use in a MFC due to its high oxidation potential, low cost and formation of water as its waste product.…”
Section: Cathode Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction of oxygen at the cathode of MFCs is recognized as one of the current bottlenecks in power production [19,[130][131][132]. Oxygen is an ideal acceptor for use in a MFC due to its high oxidation potential, low cost and formation of water as its waste product.…”
Section: Cathode Interactionsmentioning
confidence: 99%
“…The performance of a wet air cathode inoculated with a consortium of sludge and sediment microbes was increased through the interactions of the microorganisms on the cathode surface [131,139]. The use of a biocathodes has also been reported to reduce charge transfer resistance of the cathode from 188 to 17 ohms [140] and 40.2 to 12 ohms [141].…”
Section: Cathode Interactionsmentioning
confidence: 99%
“…Direct biocathodes can be based on enzymes (Topcagic and Minteer 2006;Schaetzle et al 2009) or contain microorganisms that are attached to the cathode and that accept electrons from the electrode while reducing oxygen. This last type of biocathodes has been studied in salt water as well as in freshwater (Bergel et al 2005;Clauwaert et al 2007b). Although (bio)catalyzed cathodes have been shown to catalyze oxygen reduction compared to the plain material, the open circuit potentials are still low: in the range of 0.4-0.5 V vs NHE or sometimes higher, 0.65 V vs NHE (Clauwaert et al 2007b).…”
Section: Overpotentials For Oxygen Reductionmentioning
confidence: 99%
“…This last type of biocathodes has been studied in salt water as well as in freshwater (Bergel et al 2005;Clauwaert et al 2007b). Although (bio)catalyzed cathodes have been shown to catalyze oxygen reduction compared to the plain material, the open circuit potentials are still low: in the range of 0.4-0.5 V vs NHE or sometimes higher, 0.65 V vs NHE (Clauwaert et al 2007b). …”
Section: Overpotentials For Oxygen Reductionmentioning
confidence: 99%
“…Clauwaert et al 9 realized that the reduction in oxygen at the cathode is one of the major bottlenecks of microbial fuel cells (MFCs). Freguia et al 10 found that the reduction in oxygen in the bio-cathode had improved as the anode effluent directly flowed into cathode of the double-chamber MFC.…”
Section: Introductionmentioning
confidence: 99%